Funktionsverbgefüge und ihre Stammverbkonstruktionen – ein korpusbasierter Vergleich - Fejklowicz, Urszula (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Funktionsverbgefüge are described as complex predicates with characteristic morphosyntactic and semantic features. Verbo-nominal constructions are composed of a verb component and a noun component. The construction as a whole is closely related to the derivation basis of the noun component. The present paper offers a comparison between two constructions: im Zusammenhang stehen and zusammenhängen. It has been tested if language users really take advantage of Funktionsverbgefüge properties, their syntactic and semantic behavior. The aim of this case study was to state the syntactic and semantic properties of the two construction types and their stylistic and functional benefits more precisely.
Keywords: synthetic compounds; word-formation; contrastive linguistics; German; Italian; English; word-based model approach